(untitled) (Applied Biological Research, 2016)
The present study was aimed to assess the seasonal variation in glutathione peroxidase (GPx) in seminal plasma of Karan Fries (Tharparkar x Holstein Friesian) bulls. Weekly ejaculates were collected by artificial vagina (42-45°C) during winter (December to mid February), spring (mid February-April), hot dry (May-June) and hot humid(July-August) seasons. Higher concentration of GPx was observed during hot humid season (65.74±0.93 pg mL-1) than in winter (59.30± 0.60 pg mL-1), spring (60.67±0.76 pg mL-1) and hot dry (62.14±0.90 pg mL-1) seasons. The percentage of live spermatozoa decreased during hot humid season as compared to other seasons. The acrosomal integrity also decreased during hot dry (78.7±0.6%) and hot humid (74.2 ±0.6%) seasons as compared to winter (83.1±0.6%) and spring (83.4±0.5%) seasons. The supplementation of antioxidant appears essential to Karan Fries bulls during summer season under tropical climatic conditions.